Increasing the vitamin D level of oyster mushrooms by UV light - Győrfi, J.; Kovács, A.; Szabó, A. (International Journal of Horticultural Science, 2011)
Vitamin D is essential for the human body and mushrooms are one of the natural sources of it. Many research works are aimed at enhancing the vitamin D2 content of mushrooms with UV irradiation in order to increase their vitamin D2 level, by transforming their natural ergosterol content into vitamin D2. The subjects of most of these studies are different kind of post-harvest cultivated mushrooms. In our experiment biologically active, pre-harvest oyster mushrooms were treated in the growing room with UVB and UVC light. UVB and UVC lamps (operating on 312 and 254 nm) and 6 time periods of irradiation (15, 30, 45, 60, 75 and 90 min) were used. After three consecutive days of treatments the yield were measured and samples were taken for vitamin D2 and ergosterol analysis. Data showed considerable increase (from 0,67 μg/g to 3,68 μg/g, f.w.) in vitamin D2 levels at every time period in case of both wavelengths.